Pembelajaran Pendidikan Agama Islam Jarak Jauh bagi Siswa Tunarungu pada Masa Covid-19 di Kelas XI SMALB Api Alam Pamekasan - Jamilah, Wardatul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Islamic religious education is the most important thing to be taught to all Muslims, including deaf children. However, implementing learning for deaf students is not easy, this is because their physical limitations can affect all aspects of themselves. Especially during the Covid-19 pandemic, the Indonesian government required all education practitioners to carry out distance learning. Distance learning is what makes learning for deaf students more difficult given the limitations that students have and the limitations of the conditions of the Covid-19 pandemic. This research aims to analyze learning planning, learning implementation, learning evaluation as well as supporting and inhibiting factors for distance learning for deaf students during the Covid-19 pandemic in class XI Islamic religious education subjects at SMALB Api Alam Pamekasan. The research approach used is a qualitative field approach, with descriptive analysis research type. The methods used are interviews, observation and documentation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. Checking the validity of the data is carried out through credibility tests, transferability tests, dependability tests and confirmability tests. The research results showed that learning planning was carried out by creating lesson plans that were appropriate to the students' needs and conditions. Learning is carried out online and offline. There are two learning evaluations, namely daily evaluation and semester evaluation. Consists of 3 aspects of assessment, namely cognitive, affective and psychomotor assessment. Supporting factors for PJJ include good cooperation between teachers and students' parents. And factors inhibiting PJJ include students' lack of ability to understand learning, students' erratic emotions or moods, lack of ability of students' parents to understand and explain the material that must be presented and parents lack of time to accompany students in their learning.